Parameters comparison of p-i-n and quantum well solar cells - Prażmowska, Joanna; Korbutowicz, Ryszard; Paszkiewicz, Regina; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Double gallium arsenide quantum wells (2QW) were inserted within AlxGa1–xAs barriers of the intrinsic layer of an ordinary solar cell. Structure parameters have strong influence on device performance and should be precisely controlled in order to obtain the enhancement of conversion efficiency. Computer simulations of solar cells were carried out by SimWindows program v. 1.5.0. Some parameters of optimized quantum well solar cells (QWSC) and reference p-i-n solar cell structures, like: series resistance Rs, shunt resistance Rsh, emission coefficients (n1 and n2), diffusion and recombination components of current (Jd and Jr) were compared.
Optica Applicata, Vol. 37, 2007, nr 4, s. 371-376
Keywords: optyka; quantum well solar cells (QWSC); conversion efficiency; SimWindows